Molecular cloning, sequencing and sequence analysis of Thermus thermophilus tyrosyl-tRNA synthetase - Yaremchuk, A.D.; Kovalenko, O.P.; Gudzera, О.I.; Tukalo, M.A. (Біополімери і клітина, 2004)
The gene encoding tyrosyl-tRNA synthetase (TyrRS) from the extreme thermophilic eubacterium T. thermophilus HB27 has been cloned and sequenced. The open reading frame encodes a polypeptide chain of 432 amino acid residues in length (molecular mass 48717 Da). Comparison of the amino acid sequence of the T. thermophilus TyrRS (TyrRSTT) with those of TyrRS from various organisms shows that T. thermophilus enzyme shares a branch in the philogenetic tree of eubacterial TyrRSs with the enzymes from Aquifex aeolicus, Deinococcus radiodurans, Haemophilus influenzae and Helicobacter pyroly (40-57 % amino acid identity), distinct from the branch containing Esherichia coli, Chlamydia trachomatis and Bacillus stearothermophilus, for example (24–28 % amino acid identity). The TyrRS active site domain is highly conserved, whereas a C-terminal tRNA binding domain contains only few conserved residues. But even in the active site exists one very important difference between the two groups of bacterial TyrRSs: Lys-41 in TyrRSTT (and in TyrRS from many human pathogenic bacteria) is conserved as a tyrosine in another group of bacterial TyrRSs and eukaryotic sequences including human. This knowledge could be exploited in the design of new antibiotics.